Zambia : Poverty Reduction Strategy Paper; Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report ;, 2007)
The Joint Staff Advisory Note discusses the progress in implementing the Poverty Reduction Strategy Paper (PRSP) for Zambia. The government has officially launched its second PRSP, known as the Fifth National Development Plan (FNDP) for 2006-10. The FNDP builds on the achievements of the first PRSP, for example, strong improvements in macroeconomic performance and progress in public expenditure management. FNDP has strengthened its focus on key issues, emphasizes achieving tangible results, and includes appropriate monitoring and evaluation arrangements.